Translational repression by the human iron-regulatory factor (IRF) in Saccharomyces cerevisiae. - Oliveira, C C (1993)
The regulation of the synthesis of ferritin and erythroid 5-aminolevulinate synthase in mammalian cells is mediated by the interaction of the iron regulatory factor (IRF) with a specific recognition site, the iron responsive element (IRE), in the 5' untranslated regions (UTRs) of the respective mRNAs. A new modular expression system was designed to allow reconstruction of this regulatory system in Saccharomyces cerevisiae. This comprised two components: a constitutively expressed reporter gene (luc; encoding luciferase) preceded by a 5' UTR including an IRE sequence, and an inducibly expressed cDNA encoding human IRF. Induction of the latter led to the in vivo synthesis of IRF, which in turn showed IRE-binding activity and also repressed translation of the luc mRNA bearing an IRE-containing 5' UTR. The upper stem-loop region of an IRE, with no further IRE-specific flanking sequences, sufficed for recognition and repression by IRF. Translational regulation of IRE-bearing mRNAs could also be demonstrated in cell-free yeast extracts. This work defines a minimal system for IRF/IRE translational regulation in yeast that requires no additional mammalian-specific components, thus providing direct proof that IRF functions as a translational repressor in vivo. It should be a useful tool as the basis for more detailed studies of eukaryotic translational regulation.